2020
DOI: 10.3389/fmicb.2020.00419
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Oxidase: A Potential Target for Controlling Aflatoxin Contamination and Propagation of Aspergillus flavus

Abstract: Aflatoxins are among the most hazardous natural cereal contaminants. These mycotoxins are produced by Aspergillus spp. as polyketide secondary metabolites. Aflatoxigenic fungi including A. flavus express the alternative oxidase (AOX), which introduces a branch in the cytochrome-based electron transfer chain by coupling ubiquinol oxidation directly with the reduction of O 2 to H 2 O. AOX is closely associated with fungal pathogenesis, morphogenesis, stress signaling, and drug resistance and, as recently reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
(79 reference statements)
1
15
0
Order By: Relevance
“…Among the down-regulated proteins, cytochrome c oxidase subunit Va (B8NQA4) and cytochrome C1/Cyt1 (B8MYK0) regulated oxidative phosphorylation through cytochromes. These results indicated that the down-regulated proteins may control AF production via oxidative phosphorylation, consistent with previous research ( Tian et al, 2020 ). With regard to starch and sucrose metabolism, there were nine proteins showing significant up-regulation, but no down-regulated proteins were observed in this cluster.…”
Section: Resultssupporting
confidence: 92%
“…Among the down-regulated proteins, cytochrome c oxidase subunit Va (B8NQA4) and cytochrome C1/Cyt1 (B8MYK0) regulated oxidative phosphorylation through cytochromes. These results indicated that the down-regulated proteins may control AF production via oxidative phosphorylation, consistent with previous research ( Tian et al, 2020 ). With regard to starch and sucrose metabolism, there were nine proteins showing significant up-regulation, but no down-regulated proteins were observed in this cluster.…”
Section: Resultssupporting
confidence: 92%
“…Conversely, the upregulation of alternative oxidase genes in P. cinnamomi rather than P. infestans suggest a key contribution of these enzymes in the ROS detoxification, as previously found for the oxidative stress-handling machinery of Ustilago maydis ( Juarez et al, 2006 ). Alternative oxidases are also key enzymes of the alternative respiration pathways in phytopathogenic fungi ( Tian et al, 2020 ) and their expression was upregulated by non-fermentable carbon sources (e.g., glycerol and ethanol) in C. albicans ( Huh and Kang, 2001 ). Thus, P. cinnamomi may upregulate alternative oxidase pathways, in order to mitigate the oxidative stress and to allow alternative respiration, in agreement with the normal ROS level and oxygen consumption rate previously found during tagatose incubation ( Chahed et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The alternative oxidase (AOX) is a protein localized on the matrix side of the inner mitochondrial membrane. It plays a vital role in controlling reactive oxygen species (ROS), metabolic homeostasis, cellular energy demand, redox state, and stress response in fungal cells ( Tian et al., 2020 ). Thus, AOX expression, mainly for high metabolic activity in cultures with higher glucose titers, helps the fungus cope with oxidative and osmotic stresses during fungal growth in liquid culture.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, AOX expression, mainly for high metabolic activity in cultures with higher glucose titers, helps the fungus cope with oxidative and osmotic stresses during fungal growth in liquid culture. AOX genes have been closely associated with fungal pathogenesis, morphogenesis, stress signaling, and drug resistance ( Tian et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%